Cyber Notary and the Digital Transformation of Authentic Deed Formation in Indonesia - Putri Afifah; Anggreany Arief; Muhammad Arsy (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
Abstract:This research aims to examine and describe the regulatory issues encountered by notaries in the process of drafting authentic deeds online, as well as to identify and analyze the main challenges in regulating the online execution of authentic deeds by notaries. The study adopts an empirical research method, which is based on direct observation and actual experiences in the field. The primary objective is to obtain concrete data or evidence through scientific methods such as observation, interviews, surveys, experiments, or case studies.   The research findings indicate that the regulation of Cyber Notary is stipulated in Article 15, Paragraph (3) of the UUJN; however, its implementation in Indonesia is still hindered by the lack of clear regulations. Changes are required in the definition of notarial deeds, the authority of notaries concerning electronic deeds, and adequate digital procedures. Furthermore, data security and the verification of parties’ identities are crucial to prevent cybercrime. Therefore, harmonization between the UUJN, the Electronic Information and Transactions Law (UU ITE), and other relevant regulations is key to the successful implementation of Cyber Notary. The challenges in implementing Cyber and Electronic Notary encompass substantive, structural, and legal culture aspects. Substantively, regulations must be updated to include provisions on online presence and electronic identity verification. Structurally, secure technology, integrated infrastructure, and capacity building for notary human resources are necessary. Meanwhile, from the perspective of legal culture, public trust in the security and validity of electronic transactions must be established. Consequently, inter-institutional collaboration and regulatory adjustments are essential steps to support the readiness of notaries and a reliable system. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menggambarkan pengaturan yang dihadapi oleh notaris dalam proses pembuatan akta otentik secara onlie serta untuk mengetahui dan menggambarkan tantangan utama yang ada dalam mengatur pembuatan akta otentik secara online oleh notaris. Penelitian ini menggunakan metode penelitian empiris, yaitu penelitian yang didasarkan pada pengamatan langsung atau pengalaman nyata di lapangan. Tujuan utama dari penelitian ini adalah untuk memperoleh data atau bukti konkret melalui metode ilmiah, seperti observasi, wawancara, survei, eksperimen, atau studi kasus. Hasil penelitian menunjukkan bahwa Pengaturan Cyber Notary diatur dalam Pasal 15 Ayat (3) UUJN, namun penerapannya di Indonesia masih terhambat oleh kurangnya regulasi yang jelas. Diperlukan perubahan pada definisi akta notaris, kewenangan notaris terkait akta elektronik, serta prosedur digital yang memadai. Selain itu, aspek keamanan data dan identitas para pihak sangat penting untuk mencegah kejahatan siber. Oleh karena itu, harmonisasi antara UUJN, UU ITE, dan regulasi lainnya menjadi kunci keberhasilan penerapan Cyber Notary. Tantangan implementasi Cyber dan Electronic Notary mencakup aspek substansi, struktur, dan kultur hukum. Secara substansi, regulasi harus diperbarui agar mencakup kehadiran online dan verifikasi identitas elektronik. Dari segi struktur, dibutuhkan teknologi yang aman, infrastruktur yang terintegrasi, serta peningkatan kapasitas SDM notaris. Sementara itu, dari sisi kultur hukum, perlu dibangun kepercayaan masyarakat terhadap keamanan dan keabsahan transaksi elektronik. Untuk itu, kolaborasi antar lembaga dan penyesuaian regulasi menjadi langkah penting dalam mendukung kesiapan notaris dan sistem yang andal.